Sonata para viola e piano (1962) de Francisco Mignone: a Teoria do Contorno e os aspectos da técnica de mão direita na preparação de uma performance - Daniel Ramalho Prazeres (2017)
The present work intends to evidence a little divulged piece of the repertoire of Brazilian music for viola. The sonata for viola and piano (1962) by Francisco Mignone will be object of a succinct historical investigation in the surroundings of the decade of 1960, and material for an analysis based on the theory of the contour of Michael Fridemann as well as a study of the relationship among the apects of the right hand technique: speed, pressure and point of contact. These approaches seek to elucidate interpretative possibilities and discuss their effects in the dynamic process of artistic achievement.